THE ANALYSIS OF CONNOTATIVE MEANING FOUND IN PERCY BYSSHE SHELLEY’S POEMS. - Adi Rahman (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
Most people find difficulties while studying and reading poems because a poem is full of meanings and symbols. Understanding a poem is not as easy as understanding texts of books whose meaning actually depend on the real text. To understand a poem is not enough only with lexical meaning. Thus, the reader should understand other meanings. One of the meaning that can be used to understand poems is connotative meaning because that meaning depends on what is referred to. In this study, the researcher is interested in analyzing Percy Bysshe Shelley’s poems by using connotative meaning theory and message. The objectives of this study are (1) To describe the connotative meanings are used in Percy Bysshe Shelley poems and (2) To know the message of Percy Bysshe Shelley poems which are performed to the readers. In this research, the researcher focus on connotative theory from Geoffrey leech, (2003:24). The researcher also used figurative language theory from Tengso Tjahjonobecause the theory is more detail than others. He divided figurative language into four types in generally. Those are comparison, affirmation, satire, and contradiction. Based on the result of the analysis, the researcher found in Percy Bysshe Shelley’s selected poems used connotative meaning in each line of his poems to tell the relationship between human, nature, and love. He also used various figurative language such as metaphor, personification, hyperbole, and smile to create a purpose in this poems by equating and comparing with nature around him that has a certain relationship.